La necesidad de celebrar convenios de asociación en la localidad de Bosa, para garantizar el derecho fundamental a la igualdad efectiva (2022)
The public contracting processes in Colombia allow the participation of different actors in the development of state budget execution, through the modality of association agreements, participation and significant relevance are given to non-profit entities that normally comply Not only with the experience and quality requirements established in Decree 092 of 2017, but they also show roots in the annual processes, especially with the Afro-descendant population and the different ethnic groups settled in the territory. The research methodology to be used is qualitative and interpretive, according to Hernández, Fernández and Baptista (2014) “this especially useful method uses the collection and analysis of data to refine the research questions or reveal new questions in the research process. interpretation ”, it is pertinent then to exalt the importance of this contracting modality under the understanding of the advantages it has over others and thus be able to give tools to the territorial entities so that they can succeed in choosing the appropriate modality always thinking about quality of budget execution.